Fiscal policy and economic cycles in oil-exporting countries - Husain, Aasim M.; Tazhibayeva, Kamilya; Ter-Martirosyan, Anna (IMF working paper, 2008)
This paper empirically assesses the impact of oil price shocks on the underlying non-oil economic cycle in oil-exporting countries. Panel VAR analysis and the associated impulse responses indicate that in countries where the oil sector is large in relation to the economy, oil price changes affect the economic cycle only through their impact on fiscal policy. Once fiscal policy changes are removed, oil price shocks do not have a significant independent effect on the economic cycle.